A comprehensive study of worldwide selfie-related accidental mortality: a growing problem of the modern society. Issue 4 (2nd October 2017) - Jain, Mohit J.; Mavani, Kinjal J.
Abstract: Since Oxford dictionary has described 'Selfie', selfie deaths have received a fair amount of coverage but the extent of the problem and the data behind it have not been appropriately explored. The aim of our study is to obtain epidemiological characteristics of selfie-related mortality worldwide with the objective of providing an insight to 'Why selfie', 'Why risky', 'Psychological basis' and 'measures of control.' Despite thousands of web pages, very few scientific articles are available in medical journals. So, we went online via Google search engine compiling every reported instance after confirming it and verifying the information in Wikipedia. Non-fatal injuries and non-selfie type of photography-related deaths were excluded from the study. From 2014 to mid-2016, 75 people have died while attempting selfie in 52 incidents worldwide. Mean age of the victims was 23.3 and 82% were male. India is the most affected country and Russia and US being second. Fall from height, drowning and rail accidents are the top three modes of death. Large-scale use of cell phone worldwide and underlying risk in selfie behaviour seems the culprit. Inability to compare selfie with non-selfie photography due to lack of data is definitely a limitation. Worldwide initiatives are being taken like 'NO SELFIE ZONES' but still a multifactorial approach is required before it gets too late.